Influence of roasted barley on quality of beer - Davis, Dave, author; Stone, Martha, advisor; Avens, Jack, committee member; DeVoe, Dale, committee member (Colorado State University. Libraries, 2013)
The research examined the influence of roasted barley content of beers on the quality of the resulting product. Recent researchers have indicated that moderate consumption can be a source of beer specific antioxidants, help reduce the risk of cardiovascular disease, and lower the occurrence of certain types of cancers. Beers were made with two-row malted and six-row unmalted roasted barley. Brews contained varying levels of the unmalted six-row roasted barley with the balance of the grain bill composed of two-row malted barley. They were analyzed for total phenolic content, sensory properties, and the physical properties specific gravity, color, and calculated alcohol. Four test groups were prepared with four replications of each test group for a total of 16 brews. No significant differences (P > 0.05) were found between the test brews for total phenolics. Total phenolics ranged from 314.77 to 451.72 micromoles / 100 milliliters for the test brews. Using Kuskal-Wallis one-way analysis of variance, a significant difference was found (χ2 =14.328, p = 0.00249) which demonstrated an increase in beer color as the percentage of roasted barley increased for the beer treatments. A significant difference was found in the organoleptic properties of the finished beers for total score, but not in individual categories. Perception of the bitter and burnt characteristics imparted by roasted barley appeared to increase as the percentage of roasted barley increased. This was not necessarily viewed as a detriment to the beer, but as an increase in complexity that added to the overall flavor and balance of the beer. There was a linear progression (P > 0.05) in the scores for aroma and appearance as the percentage of roasted barley increased. No significant differences (P > 0.05) were found in original or final specific gravity or within calculated alcohol values.